Optimism and Longevity Beyond Age 85. (20th February 2021) - Jacobs, Jeremy M; Maaravi, Yoram; Stessman, Jochanan
Abstract: Background: Optimism is associated with health benefits and improved survival among adults older than 65 years. Whether or not optimism beyond age 85 continues to confer survival benefits is poorly documented. We examine the hypothesis that being optimistic at ages 85 and 90 is associated with improved survival. Method: The Jerusalem Longitudinal Study (1990–2020) assessed comorbidity, depression, cognition, social and functional status, and 5-year mortality among a representative community sample, born during 1920–1921, at age 85 ( n = 1096) and age 90 ( n = 533). Overall optimism (Op-Total) was measured using a validated 7-item score from the Scale of Subjective Wellbeing for Older Persons. The 4 questions concerning positive future expectations (Op-Future) and 3 questions concerning positive experiences (Op-Happy) were also analyzed separately. We determined unadjusted mortality hazards ratios and also adjusted for gender, financial difficulty, marital status, educational status, activities of daily living dependence, physical activity, diabetes mellitus, hypertension, ischemic heart disease, cognitive impairment, and depression. Results: Between ages 85–90 and 90–95 years, 33.2% (364/1096) and 44.3% (236/533) people died, respectively. All mean optimism scores declined from age 85 to 90, with males significantly more optimistic than females throughout. All measures of optimism (Op-Total, Op-Future, and Op-Happy) at ages 85 and 90 were significantly associated with improved 5-year survival from age 85 to 90 and 90 to 95, respectively, in both unadjusted and adjusted models. Findings remained unchanged after separately excluding depressed subjects, cognitively impaired subjects, and subjects dying within 6 months from baseline. Conclusions: These finding support the hypothesis that being optimistic continues to confer a survival benefit irrespective of advancing age.